How does FinTech development drive corporate innovation? Fresh evidence from the perspective of financial supply - Lee, Chi-Chuan; Fang, Lei; Zhao, Jinsong; Yu, Chin-Hsien; Zhang, Jian (Technological and Economic Development of Economy, 2025)
By constructing a city-level financial-technology (FinTech) development dataset, this study examines the impact of FinTech on corporate-innovation behavior from a financial-supply perspective. The results reveal that FinTech promotes corporate innovation by reducing corporate-financing constraints and financing costs, alleviating information asymmetry, and expanding financing channels. This promotion effect is more pronounced for private, small, and young firms, firms with fewer fixed assets, and those located in low-regulation intensity areas. Moreover, credit-based FinTech companies have a greater impact on business innovation. In addition, bank deregulation and increased bank competition crowd out the financial supply of FinTech for innovation financing. Knowledge of these impacts can help corporate managers, governments, and financial regulators to formulate more effective development strategies to promote corporate innovation.First published online 15 November 2024